1980
DOI: 10.1038/287736a0
|View full text |Cite
|
Sign up to set email alerts
|

Localization of metabolites in animals using 31P topical magnetic resonance

Abstract: High-resolution phosphorous (31P)-NMR spectra of biological molecules provide detailed information about the metabolism of living systems. Although the NMR method is non-destructive, all studies so far, with two exceptions, have been carried out on excised, perfused organs and tissues or have required some form of surgery for in situ measurements. The use of 'surface' radiofrequency coils does not require surgery, but is best suited for tissues close to the surface of the animals. We describe here 'topical mag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
63
0
2

Year Published

1985
1985
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 232 publications
(65 citation statements)
references
References 9 publications
0
63
0
2
Order By: Relevance
“…But the conventional NMR spectrometer had several limitations, when used with biological tissue. Recently topical magnetic resonance (TMR) was developed and allowed us to measure phosphorous compounds in the profound organs, or a part of the whole body (TANAKA et al, 1974;GORDON et al, 1980). TMR technique provided in vivo information in the muscle RADDA et al, 1982), the kidney (BALABAN et al, 1981), the tumor of rat (GRIFFITHS et al, 1981), and the brain (NARUSE et al, 1983).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…But the conventional NMR spectrometer had several limitations, when used with biological tissue. Recently topical magnetic resonance (TMR) was developed and allowed us to measure phosphorous compounds in the profound organs, or a part of the whole body (TANAKA et al, 1974;GORDON et al, 1980). TMR technique provided in vivo information in the muscle RADDA et al, 1982), the kidney (BALABAN et al, 1981), the tumor of rat (GRIFFITHS et al, 1981), and the brain (NARUSE et al, 1983).…”
Section: Discussionmentioning
confidence: 99%
“…It is a method of magnetic focusing (TANAKA et al, 1974). GoRDON et al (1980) reported the phosphorous compound of an in vivo profound organ by the TMR.…”
mentioning
confidence: 99%
“…After early attempts on whole animals [14], numerous studies of live, intact animals took place in the 1970s to investigate anatomy, biochemistry, and physiology in vivo [38][39][40][41], also using perfused organs (e.g., [42][43][44]). In 1979, Britton Chance at University of Pennsylvania (PA, USA), contacted OI (UK) to design and build the first horizontal 1.5 T/20 cm magnet for metabolic research.…”
Section: Biomedical and Preclinical Mri And Mrs Researchmentioning
confidence: 99%
“…It allows the study of physiological processes in a non-destructive and non-invasive manner. Particularly 31 P-NMR proved revealing for the measurement of metabolite concentrations and pH in tissue (Gordon et al 1980(Gordon et al , 1982Ackerman et al 1980;Gadian, 1982). Although less resolution is required for in vivo spectroscopy than for imaging, such a simple field-focusing technique is often inadequate for investigating smaller organs, and alternative approaches have been proposed for better localizing the area of observation, as described below.…”
Section: Sensitive-point Techniquementioning
confidence: 99%